The study of dietary diversity score in children between 6 months to 23 months: a hospital based study - N., Divya; K. V., Rajanish; J., Malavika; Sharma, Aarti (International Journal of Contemporary Pediatrics, 2018)
Background: Dietary diversity is a qualitative measure of food consumption that reflects household access to a variety of foods and is also a proxy for nutrient adequacy of diet of individual. Breast-feeding and complementary feeding practices are fundamental to children’s survival and development. Feeding practices have an impact on physical growth, which is one of the best indicators of children’s well-being. However, the relation between the quality of feeding practices during early age and nutritional status are difficult to establish, and, depending on the context and overall living conditions, the influence of feeding factors on children’s nutritional status can vary considerably. This study helps us to assess the dietary diversity score by simple food count method which is a good indicator of adequate micronutrient intake. Methods: The study was a retrospective study conducted on babies between 6 months to 23 months of age presenting in Paediatric outpatient Department. Data was collected by 24-hour recall method for 3 days and an average. Results: 30% of subjects had weight for age below 2 SD and 8% had length for age below 2 SD. Dietary diversity Score of 1and 6 in 8%, 2 in 48%, 3 and 5 in 6%, 4 in 24% was noted. The average scoring was low among 6-9 and10-12 months and it increased between 13-23 months. With increase in age there was increase in dietary diversity score and vice versa. Conclusions: Limited diversity in complementary foods is a strong predictor of the nutritional status of children. Inclusion of a variety of food groups may be more essential to improve child’s nutritional status.